Role of diagnostic hysteroscopy in abnormal uterine bleeding - Singh, Swati; Taneja, Bal Krishan; Singh, Prem; Ahlawat, Ravinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to correlate hysteroscopic findings with histopathological findings in women with abnormal uterine bleeding and to study the accuracy of hysteroscopy in abnormal uterine bleeding. Methods: Settings: tertiary care hospital. Study design: prospective study. A prospective study was carried out in the Department of Obstetrics and Gynaecology at MMIMSR, Mullana, Ambala, from May 2011 to September 2013. 100 cases were selected for this study from patients who were admitted with history of abnormal uterine bleeding. Hysteroscopic examination was done in all patients post-menstrually, whenever possible, except in those cases where menstrual cycles were grossly irregular or patients came with continuous bleeding per vaginum. The patients then underwent dilatation and curettage and curettings was sent for histopathological examination. The correlation between findings on hysteroscopy and histopathological examination was done. Results: On hysteroscopy, 48% of the patients had either proliferative or secretory picture which was grouped as normal. The rest 52% of patients had some abnormality. Hyperplasia was the most common finding which was seen in 26% patients. The other findings included endometrial polyp 8%, myoma or myomatous polyp 7%, atrophic endometrium 4%, endometrial carcinoma, misplaced IUCD, and synechiae comprising 2% each and tubercular endometritis 1%. Conclusions: Hysteroscopy has a high sensitivity i.e. it can supplement and enhance the accuracy of tissue diagnosis. So, hysteroscopically directed biopsy would be an ideal procedure in abnormal uterine bleeding wherever facilities are available.